Peningkatan Kualitas Manusia dalam Implementasi Tujuan Pembangunan Berkelanjutan di Provinsi Sumatera Utara - Rita Herawaty Bangun (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2020)
The development of human resources is one of the Indonesian priority programs for five years later. The high quality of human resources to be determining progress and changing to better in the region, including the province of Sumatera Utara. To know the quality of human resources, there are many indicator influences this human quality. This study aims to analyze the socio-economic indicators consisting of poverty, unemployment, health, education, and income to the human development index (HDI) in Sumatra Utara Province. This research uses cross-section data sourced from publications published by the Central Statistics Agency (BPS) that describe the condition of city districts in Sumatra Utara Province. The analytical method was used in multiple linear regression analysis techniques. The results of research show that indicators of poverty, unemployment, health, education, and decent living standards have a strong influence that is equal to 99.83 percent of HDI, while 0.17 percent is influenced by other variables outside the model. Based on the results of simultaneous and partial testing all variables of poverty, unemployment, health, education, and income have a significant effect on HDI in Sumatra Utara. Achieving increased human development as an implementation of sustainable development goals must be a priority scale in the formulation of regional development policy and planning in the Province of North Sumatra, particularly in the aspects of health, education, and community income. Improvements in the aspects of health, education and economic growth will drive the achievement of the quality of human development in Sumatra Utara.